PSXIII-24 A Survey of Australian Shepherd Breeding Practices and Genetic Diversity. (7th December 2018) - Bennett-Wimbush, K; Suagee-Bedore, J; Sharp, C
Abstract: A survey (n = 181) was conducted to study factors affecting litter size, health testing trends, and genetic diversity in Australian Shepherds. A voluntary Qualtrics survey was distributed via online links through Australian Shepherd Club of America, Australian Shepherd Heath and Genetics Institute, and social media from June through December 2017. Data used in analysis were obtained from survey results except coefficients of inbreeding (CQI), which were calculated using a 10 generation database (BreedMate PedX) from submitted registration names. A mixed model (SAS) was used to evaluate main effects of breeding method, dam weight, dam age, dam pedigree type, and gestation length on litter size, as well as differences in dam and sire CQI by pedigree type (Conformation, Working, Performance, Blended). Respondents represented breeders from North America, Europe and Australia. Breeders reported testing for hip dysplasia, elbow dysplasia, and eye defects in breeding stock 99, 91.7, and 97.2% of the time respectively. Multiple drug resistant gene (92.8%)) and heredity cataracts (84%) were the most common genetic tests. The average litter produced 6.6 puppies. Breeding method, dam weight, dam pedigree type, and gestation length had no effect on litter size. A quadratic relationship between litter size and dam age was observed with larger litters (P < 0.05) in young dams (ages 2–3; 6.9 ± 0.34) and older dams (ages 6–7; 7.5 ± 0.42) compared to dams 3 to 5 years of age (6.4 ± 0.26). Dam CQI was higher in conformation pedigrees (14.1% ± 1.0) compared to working pedigrees (8.9% ± 1.1; P < 0.001) and blended pedigrees (11.1% ± 1.0; P < 0.05). Sire CQIs in working pedigrees (9.4% ± 1.1) were lower (P < 0.05) than blended (13% ± 1.5) or conformation (12.3% ± 0.9) pedigrees. A more diverse and larger sampling, including pet breeders is recommended.